EFEKTIVITAS NAZHIR DALAM PENGELOLAAN DAN PENGEMBANGAN HARTA WAKAF PESANTREN - muhammad arif fauzi (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Waqf is a legal action of a person, group, or legal entity that separates part of their property for the purpose of worship or other purposes according to Islamic teachings. This study uses a field research method with a descriptive-qualitative approach. Primary data is obtained directly from primary sources, while secondary data comes from indirect sources. Data collection techniques include observation, interviews, and documentation, with analysis using descriptive-analytical methods. The results of the study show that the role of nazhir at YPP Miftahul Ulum in Bengkak Village has not been optimal. The appointment of nazhir is still carried out traditionally, choosing parents who are considered religious and able to manage waqf land, but do not meet the ideal criteria. The supporting factors for waqf management are references to Law No. 41 of 2004 concerning Waqf, while obstacles include internal factors, such as limited human resources, and external factors, such as lack of attention from the government and the surrounding community. The impact of supporting factors allows nazhir to adjust its duties and functions according to the law, while inhibiting factors cause the management and development of waqf land to not be optimal.